Early years spending update: Budget reforms and beyond - Elaine Drayton; Christine Farquharson (Institute for Fiscal Studies (IFS), 2023)
The last 25 years has seen a transformation in how early years education and childcare is approached in England. The establishment and subsequent expansions of a "free entitlement" to funded early education and childcare have seen early years spending quadruple over the last 25 years, and a major expansion of support announced at the March 2023 Budget will lead total spending to more than double. However, there are considerable challenges with the design, delivery and distributional consequences of these reforms. In this report, we examine how total spending on the early years system and on the free entitlement has changed; explore the impact of demographic changes; set out forecasts for how total spending and spending per hour might change going forward; and analyse some of the opportunities and challenges with the Budget reforms.
Keywords: 330; Education and skills; Education spending; Childcare and early years; Early childhood development; Education; Family; Government spending; Labour supply and workforce; Trends